Optimalisasi Potensi Wisata Religi Situ Lengkong Untuk Peningkatan Ekonomi Lokal di Desa Panjalu Kabupaten Ciamis - Dudi Badruzaman; Rajaminsah (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
This research aims to explore and optimize the potential for religious tourism in Situ Lengkong, Panjalu Village, Ciamis Regency, with a focus on efforts to improve the local economy. Situ Lengkong is a historical and religious site that has high cultural value and is a potential tourist attraction. However, this potential has not been fully utilized optimally to support village economic growth. This research method uses a qualitative approach with interview techniques, observation and documentation studies. The data obtained was analyzed to identify strengths, weaknesses, opportunities and threats (SWOT) related to the development of religious tourism in the area. The research results show that the potential for Situ Lengkong religious tourism can have a positive impact on the local economy through infrastructure development, more effective promotion, and community involvement in tourism management. The resulting recommendations include planning and building supporting facilities, increasing human resource capacity through training, as well as marketing strategies to attract tourists. It is hoped that this research can be a guide for related parties in developing the religious tourism potential of Situ Lengkong, so that it can encourage local economic growth and improve the welfare of the people of Panjalu Village